Previsão da estrutura a termo de cupom cambial - Barbosa, Diego Makasevicius (2017)
This paper proposes to apply a similar framework adopted by Diebold and Li (2006) to forecast the Brazilian term structure of the US dollar-denominated interest rates, which have been done through the well-known three factors model developed by Nelson-Siegel. The methodology used to find the lambda factor, which drives the decay velocity of interest rates, was the rolling window optimization where for each forecast was calculated the lambda that minimizes the root mean square error (RMSE) of Nelson and Siegel fit. Furthermore, an autoregressive model was used to estimate the latent factors and, consequently, the interest rate. The results obtained were analogous to those found by Diebold and Li, where the authors verified a good predictive capacity for the model when compared to the random walk and other models used as benchmark.